2021
DOI: 10.3390/ijgi10060395
|View full text |Cite
|
Sign up to set email alerts
|

Population Mobility and the Transmission Risk of the COVID-19 in Wuhan, China

Abstract: At the beginning of 2020, a suddenly appearing novel coronavirus (COVID-19) rapidly spread around the world. The outbreak of the COVID-19 pandemic in China occurred during the Spring Festival when a large number of migrants traveled between cities, which greatly increased the infection risk of COVID-19 across the country. Financially supported by the Wuhan government, and based on cellphone signaling data from Unicom (a mobile phone carrier) and Baidu location-based data, this paper analyzed the effects that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For each 1% increase of population inflows, the number of confirmed cases is predicted to increase by 5.98%. Consequently, the quarantine policy has been effectively reduced the rate of disease spread within the country [ 19 ]. Besides, studies indicated that the continuous UK government’s guidance to avoid non-essential travel, combined with the closure of schools and reduced operation of London Underground and national railway services, contributed to a continuous reduction in human mobility and effectively contained the pandemic during the first wave [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For each 1% increase of population inflows, the number of confirmed cases is predicted to increase by 5.98%. Consequently, the quarantine policy has been effectively reduced the rate of disease spread within the country [ 19 ]. Besides, studies indicated that the continuous UK government’s guidance to avoid non-essential travel, combined with the closure of schools and reduced operation of London Underground and national railway services, contributed to a continuous reduction in human mobility and effectively contained the pandemic during the first wave [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“… Mobility data can be misleading, as they do not always equate to risk of infection, because certain activities may suppose more risk of infection than others, regardless of the level of mobility required for each of them. For example, in 46 it is mentioned that markets and other shopping malls with frequent visitors were areas with high risk of infection (in the case of Wuhan, China), so, in general, mobility to these types of places may suppose a higher exposure to the disease. In addition, we only had the actual data on Wednesdays and Sundays, from which we had to infer the values for the rest of the days.…”
Section: Datamentioning
confidence: 99%
“…The outbreak of COVID-19 came during the Spring Festival in China, which means that many people need to travel from city to city every day. The large population and the advanced public transportation, including the intro and inter-city mobility, make it easy to lead a person carrying the COVID-19 spread to the other cities [35]. Besides, globalization has altered the way we live and earn our livelihood.…”
Section: Covid-19mentioning
confidence: 99%